The Night Operator - Packard, Frank L. (Frank Lucius), 1877-1942 (Salt Lake City, UT : Project Gutenberg, 2010)
"The Night Operator" by Frank L. Packard is a novel written in the early 20th century. The story introduces readers to Toddles, a young, aspiring newsboy on the Hill Division of a railroad, who dreams of becoming a legitimate railroader despite his small stature and the ridicule he faces from others. The narrative explores themes of ambition, resilience, and the harsh realities of working in the rail industry. The opening of the story sets up Toddles' struggle for respect and recognition within the tough environment of the railroad. Initially, he is portrayed as an outsider trying to carve out a place for himself while dealing with the bullying of a conductor named Hawkeye. The narrative is filled with vivid descriptions of the railroad setting and the challenges faced by the workers. As the chapter unfolds, Toddles' determined spirit shines through, revealing his longing to transcend his nickname and prove himself worthy of a career in railroading. The reader is left with an understanding that Toddles' journey will entail overcoming both external obstacles and his internal struggles for acceptance and purpose. (This is an automatically generated summary.)
The night operator -- Owslet and the 1601 -- The apotheosis of Sammy Durgan -- The wrecking boss -- The man who squealed -- The age limit -- "The devil and all his works" -- On the night wire -- The other fellow's job -- The Rat River Special.
Release date is 2010-09-04
Produced by Al Haines
Keywords: Fiction; Short stories; Railroad stories